2018
DOI: 10.1016/j.aprim.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia en la realización de mamografías en España: análisis por comunidades 2006-2014 y factores que influyen

Abstract: Performing mammography has increased significantly from 2006 to 2014, although there are still differences between autonomous communities, with Ceuta and Melilla being the least percentage of performed mammography. The factors that are related to greater performed mammography are: higher educational level, higher social class, married civil status, Spanish nationality and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
1
7
0
1
Order By: Relevance
“…In this study, the sociodemographic variables that are most associated with FOBT participation are higher education, higher socioeconomic level, being married, and age [11,34,35]. These variables are consistent with other screening programs carried out in Spain [36,37].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the sociodemographic variables that are most associated with FOBT participation are higher education, higher socioeconomic level, being married, and age [11,34,35]. These variables are consistent with other screening programs carried out in Spain [36,37].…”
Section: Discussionsupporting
confidence: 80%
“…These results are similar to the study conducted by Audi (2016), [ 24 ], who identified low prevalence of both cervical cancer screening and mammograms. Several factors are associated with low number of mammograms, including being single, having little education, being of low social class, lack of knowledge of prevention methods, and lack of access to free services [ 40 ]. Due to the high percentages of young women in prison, there are great consequences in not carrying out the appropriate breast cancer screening program [ 24 ]; screening has been demonstrated to be an essential strategy for reducing breast cancer mortality in women aged 40 to 49 years old [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,22,23 Spanish women from higher economic classes, for instance, had 1.4 times more probability of having the examination than those in lower economic classes. 24 It is important to reflect on the extent to which socio-economic status has been an important factor for women's adherence to prevention practices. 10,22,23 It can be seen that the higher a woman's socioeconomic level, the greater the prevalence of medical appointments and, therefore, the greater the opportunity for requesting the health professional to perform the examination.…”
Section: Discussionmentioning
confidence: 99%